2012
DOI: 10.1007/s10517-012-1689-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cellular Mechanisms of Peptide Regulation of Melatonin Synthesis in Pinealocyte Culture

Abstract: The effects of epithalone and vilone peptides on the synthesis of melatonin and factors involved in this process, arylalkylamine-N-acetyltransferase (AANAT) enzyme and pCREB transcription protein, were studied in rat pinealocyte culture. Epithalone stimulated AANAT and pCREB synthesis and increased melatonin level in culture medium. Simultaneous addition of norepinephrine and peptides into the culture potentiated the expression of AANAT and pCREB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Increased melatonin synthesis in pineal gland during aging. 33,34 3. Induced retinal cells differentiation, retinaprotector.…”
Section: Kementioning
confidence: 99%
“…Increased melatonin synthesis in pineal gland during aging. 33,34 3. Induced retinal cells differentiation, retinaprotector.…”
Section: Kementioning
confidence: 99%
“…The tetrapeptide epitalon in in vivo and in vitro studies has antioxidant activity, regulates the functions of the pineal gland and melatonin synthesis, stimulates neuronal differentiation , has immunostimulating properties, reduces the risk of the development of tumor diseases, regulates the functional activity of the neuroimmunoendocrine system, helps to increase the telomere length in normal fibroblasts and blood and to overcome the Hayflick limit [3,5,7,14,21]. The goal of the work was to study the effect of the peptides vilon (KE) and epitalon (AEDG) on the expression of the ribosome protein L7A and the area of mitochondrial staining with MitoTracker Red in cell cultures of the human thymus and pineal gland.…”
Section: Ribosome Functioning With Agingmentioning
confidence: 99%
“…It was shown that the KE peptide regulates the expression of the EPS15, MCM10 homologue, Culline 5, APG5L, FUSED, ZNF01, FLJ12848 fis, ITPK1, SLC7A6, FLJ22439 fis, KIAA69799, FIA, KIAA690099, FLA2 peptides, FLJ10914, Gdap1, MSTP028, MLLT3 and PEPP2, and the synthesis of cytoskeleton proteins, cell proliferation and metabolism, which explains its high biological activity [ 103 ]. The tetrapeptide AEDG (Epitalon) stimulates the activity of the neuroimmunoendocrine system, normalizing the functions of the thymus and cardiovascular system in pathology and ageing through regulation of melatonin synthesis [ 104 ]. Due to its ability to regulate melatonin synthesis, the AEDG peptide can be considered as one of the possible agents in complex COVID-19 therapy.…”
Section: Main Textmentioning
confidence: 99%